25 Years of increased politicisation of UK policing reform - Grieve, John G. D. (International journal of police science & management, 2024)
The past 25 years has seen the greatest attempted political shifts in the reform, governance and character of UK policing in nearly 200 years. This article takes a broad, but incomplete, look at that increased trajectory of party politics involvement in changes in British policing, the possible effect on governance, operational independence and leadership, and the probable impact of those activities on tactical effectiveness (for example, in performance, community engagement, discipline, morale, retention and recruitment). It is the increased trajectory and significance of party politics that has created a paradigm shift in the British policing model and impacted on contemporary interpretations of the wrongly called Peelian Policing Principles. This article seeks to show that Savage’s model of police reform, as a conjunction of driving forces, is useful in exploring the primary use made, over the past 25 years, of the politicisation of police reform by the other five elements of the model. It also seeks to identify what we can learn from this exploration for the future of police reform. Nothing of what follows here signifies anything but disgust at the ghastly behaviour of some criminals in police uniforms. It comprises some evidence for use at a possible Labour ‘root and branch reform of the MPS’. This proposal might take up the misguided suggestion to disband the Metropolitan Police Service (MPS), as a result of possible extinction-level events for the 200-year-old MPS experiment in policing and will inevitably and irrevocably lead to the destruction of the British policing model – one of the global pillars of democracy. Brown also offered some more effective possible reforms using Savage’s model.